Is poor global processing a transdiagnostic feature of Body Dysmorphic Disorder and Anorexia Nervosa? A meta-analysis. (June 2021) - Lang, Katie; Kerr-Gaffney, Jess; Hodsoll, John; Jassi, Amita; Tchanturia, Kate; Krebs, Georgina
Highlights: Body image disturbance is a cardinal feature of Body Dysmorphic Disorder and Anorexia Nervosa. Poor global integration in visual processing may underlie distorted body image in these disorders. Two meta-analyses examined the extent to which poor global processing is evident in BDD and in AN. Poorer global processing was observed in BDD and AN compared to healthy controls. Poor global processing was more exacerbated in AN than in with BDD. Abstract: Body dysmorphic disorder (BDD) and anorexia nervosa (AN) are characterised by body image disturbance. It has been suggested that poor global integration in visual processing may underlie distorted body image, but empirical studies have yielded mixed results. The current study involved two meta-analyses aimed at examining the extent to which poor global processing is evident in BDD and AN. Studies were identified through a systematic literature search up to October 2020. The BDD search yielded 16 studies and the AN search yielded 18 studies. Random-effect models demonstrated a small pooled effect size for BDD ( g = −0.44, 95 % CI −0.70, −0.17, p < 0.001) and a moderate pooled effect size for AN ( g = −0.63, 95 % CI −0.77, −0.49, p  <  .001), with no evidence of significant publication bias for either. The results provide evidence that poor global processing is a transdiagnostic feature of both BDD and AN, although effects may be more pronounced in AN. Our findings highlight the possibility that interventions aimed at promoting global visual processing could prove beneficial in disorders characterised by distorted body image.